Experimental Study on Microbial Fouling Inhibition Performance of Ni‐P‐NanoTiO2 Composite Surfaces. Issue 7 (24th April 2020) - Liu, Zuodong; Li, Siqi; Xing, Weiwei; Xu, Zhiming
Abstract: Microbial fouling of heat exchangers causes serious issues including increased fuel consumption, flow resistance, and maintenance cost expenditure. Composite Ni‐P‐nanoTiO2 coatings were prepared for inhibiting and mitigating the heat exchanger microbial fouling deposition. The surface energy components and wall adhesion work of microbial fouling medium had a significant effect on the microbial fouling deposition process. Compared with carbon steel coupons, the microbial fouling deposition on Ni‐P‐nanoTiO2 coatings was reduced by about 90 % and the wall adhesion work and microbial fouling deposition rate of these coatings were less. The Ni‐P‐nanoTiO2 coatings might not only be advantageous for controlling the initial microbial adhesion, but also effective for reducing the fouling deposition rate. Abstract : The microbial fouling inhibition performance of composite Ni‐P‐nanoTiO2 coatings was investigated experimentally. The prepared Ni‐P‐nanoTiO2 surfaces reduced the microbial fouling adhesion by ∼ 90 %. The effect of surface energy components and wall adhesion work on microbial fouling process was discussed. This surface technology could be practical for fouling inhibition and mitigation.